The effect of investment in human resources to report on internal control over financial reporting of listed companies in Tehran Stock Exchange - Ali Emami Meibodi; Reza Jamei; Ghasem Najafi; aref behrooz (پژوهش‌های برنامه و توسعه)
The purpose of this study is to evaluate the of investment in human resources to report on internal control over financial reporting. The purpose of this study is applied in nature, descriptive - correlation. In this study, financial data of 60 companies listed in Tehran Stock Exchange, which have offered reported internal control during the period 2017 to 2019 have been investigated. Software was used to analyze the results is spss22. In this study 10 examined the hypothesis that all hypotheses have been confirmed as part of my thesis. To test the hypotheses of this study is the use of regression analysis and Pearson. According to the results of hypothesis testing can be concluded that human resource investment companies reporting internal controls are effective and to achieve better internal control report can be invest in human resources. Results indicate that human resources is the most valuable corporate resource that meaning given to the field of human resources and organizational goals provide.